Effectiveness of Administrative Services at SMK Negeri 6 Makassar - Sulastri, Sulastri; Saleh, Sirajuddin; Jamaluddin, Jamaluddin (International Journal of Administration and Education, 2024)
The effectiveness of administrative services has the ability to provide efficient, responsive, and quality administrative services to all students in the school environment. This includes various aspects, such as student administration management, financial data management, new student admissions, school inventory management, and other administrative support.  This study aims to determine the effectiveness of administrative services at SMK Negeri 6 Makassar. This research is qualitative. focusing on service procedures, service time, service costs, service products, facilities and infrastructure, and service officer competence. Based on the results of this study, it is shown that the effectiveness of administrative services at SMK Negeri 6 Makassar is categorized as Good. This can be seen from a number of factors or indicators that describe administrative services. Service procedures in schools are categorized as good because they have provided satisfactory services for students, as shown by effective communication between students and administrative staff, as well as the implementation of structured procedures, which are key factors in the success of the service. Service time is categorized as poor because students feel that despite efforts to improve service time efficiency, there are still various obstacles in implementation in the field. The main obstacles include the willingness of the principal's signature and the absence of service staff. Administrative service fees are categorized as good because the fees have been regulated according to school policy. Not all services are charged, school administration is categorized as good because the administration has tried to provide comprehensive and efficient services to meet various needs of students. Adequate facilities are categorized as good because they not only help in administrative services, but also support student learning as a whole, even though the facilities and infrastructure in the administration are quite good, there is a need for improvement and updating of equipment to further increase the effectiveness of administrative services and support student learning. The competence of Service Officers is categorized as good because they have technical and non-technical competence, service officers can carry out their duties more effectively and efficiently, and provide optimal service to students and all parties involved in the school.